Studies on walking behaviour of people and their implications to planning the urban form a case study of barangay Industrial Valley Complex, Marikina City - Reside, Juan Miguel E.; Yap, David Leonides T.; Lidasan, Hussein S.; Jose, Maria Corazon P. (Quezon City School of Urban and Regional Planning, University of the Philippines Diliman, 2018)
This study attempts to explain the walking of people within Sitio Olandes, Monte Vista Subdivision, Cinco Hermanos Subdivision and Industrial Valley Subdivision, collectively known as Barangay Industrial Valley Complex (IVC) Marikina City. The existing urban form of the barangay and results of interviews and discussions conducted with residents of the barangay were correlated to the Hierachy of Walking Needs as developed by Alfonso (2005). Furthermore, this study examines the possible implications of certain socio-economic factors to the walking behavior of respondents. Analysis of data shows that age, health, and wealth all seem to impact walking behavior. Likewise, issues of safety and accessibility are seen as factors which influence the decision to walk. In fact, many respondents who claim to feel safe in their surroundings are more likely to prefer to walk compared to those who claim to feel unsafe. Respondents from Sitio Olandes were observed to prefer to walk more compared to residents from the other three areas within the barangay. This is likely due to their lack of alternative modes of travel and other resources such as money. Furthermore, results from Multinomial Logistic Regression analysis reveal that the walking behavior of respondents from the barangay does not strictly correlate with Alfonzo's Hierarchy of Walking Needs. In fact, based on study results, respondents tend to value accessibility above all others. In fact, based on study results, respondents accessibility above all others. This suggests that respondents value the presence of activity centers such as parks, shops, and other government and educational institutions within their community, more than the presence of pedestrian infrastructure such as sidewalks. Comfort and feasibility of the walking trip were also factors considered by respondents when deciding to walk or not. The elements of pleasurability and safety were considered to be the least influential factors.The urban form of the barangay does impact the walking preferences of its people. Pedestrian infrastructure and other safety features such as pedestrian lanes are still important aspects which encourage people to walk, although it is evident from this study that the element of diversity in the urban form is primarily what effects the decision to walk or not. Results show that the diverse mix of shops, educational and religious institutions, recreational areas, and government offices all influence a person's decision to walk. This diversity creates a healthy environment for interaction with both social and economic benefits. Based on the study findings, it is recommended that pedestrian- accessible parks and other centers of activity need to be established if walking is to be encouraged in this area. Developing a gender- and age-neutral space fit for study, work and play altogether seems to be the most appropriate development for the barangay, not only to encourage walking (especially for those in the gated communities), but also socialization and meaningful interaction. However, in planning for future developments, city planners and officials should be mindful of the needs of the community, taking into account the socio-economic profile of its residents, as well as the potential for dynamic changes within the barangay across time.
Thesis (M.A. Urban and Regional Planning)--University of the Philippines Diliman
Keywords: Walking -- Philippines -- Marikina City; Fitness walking -- Philippines -- Marikina City